VD_FINDINFO Décision / 2013 / 595 vom 16. Mai 2013 - VD Tribunal cantonal (2013)
DÉFAUTCONTUMACE, OPPOSITIONPROCÉDURE, CITATION À COMPARAÎTRE | 205 CPP (CH), 356 al. 2 CPP (CH), 356 al. 4 CPP (CH), 356 CPP (CH)